Motivators and barriers to mouthguard compliance by adult Gaelic football athletes. - Aoife Burke; Niall O'Connor; Niall Duffy; Katie Holohan; Enda F Whyte; Siobhán O'Connor (PLoS ONE)
Introduction Dental injuries contribute to 57% of reported maxillofacial injuries in Gaelic Football, with associated psychological and economic impacts on the affected athletes. Mouthguards have been developed in efforts to mitigate the incidence and severity of dental injuries, and use is mandatory in Gaelic Football. Dental claims have reduced by over 50% since mouthguards became mandatory, but costs of dental injuries are still prevalent. The aim of this study was to determine the mouthguard compliance rates in adult Gaelic Football players, as well as the motivations and barriers to compliance. Methods This cross-sectional study utilised an online survey to determine the self-reported compliance of adult Gaelic Footballers with mouthguard use, the perceived peer compliance, and the motivations and barriers to compliance. Chi-square tests were used to examine differences between sex and between elite and sub-elite players. Results A total of 545 Gaelic Footballers completed the survey. During training, 22% of players reported to always wear a mouthguard, with 48% never wearing it, and 30% occasionally wearing it. For games, 48% of players reported to wear a mouthguard, with 11% never wearing it and 41% occasionally wearing it. Motivating factors included teeth protection, gum protection and the rules of the game. The main barriers were discomfort, difficulty breathing and difficulty speaking. Females had significantly poorer compliance in training, but had significantly better compliance in games when compared to males. Conclusion Mouthguard compliance is relatively poor amongst adult Gaelic Football players. Although compliance improves for games compared to training, there are still 1 in 2 players not wearing a mouthguard for games. Discomfort and challenges with breathing and speaking suggest that players may benefit from having a custom-fit mouthguard. Coaches, refereeing officials and governing bodies should strive to implement the rules more often and improve education around the benefits of mouthguard use within the sport.